Productive Zakat as a Socio-Economic Instrument: A Bibliometric and Systematic Literature Review - Rina Desiana; Umi Julaihah; Siswanto; Jadzil Baihaqi (Al-Tijary, 2026)
Although productive zakat is recognised as a crucial instrument for poverty alleviation, systematic synthesis regarding the mapping of literature and its conceptual evolution is still limited, where field practices remain fragmented and dominated by consumptive aid. This study aims to evaluate the academic landscape of productive zakat, identify research trends, and investigate its conceptual transformation as an Islamic public financial instrument for sustainable poverty alleviation. A hybrid approach combining Systematic Literature Review (SLR) and bibliometric analysis was used in this study. Following the PRISMA framework, the final sample of 33 Scopus-indexed articles published up to mid-2026 was filtered and visualised using VOSviewer software. The research results show that productive zakat research has consistently evolved from simple linear evaluations to complex socio-economic systems rooted in the ijtihad of Maqāṣid al-Sharīʿah. The theoretical synthesis reveals that direct financial intervention does not automatically guarantee an improvement in welfare; rather, it requires critical mediating variables such as the growth of micro-enterprises and the success of Sharia-compliant businesses. Additionally, the keyword analysis highlights a shift in emphasis towards institutional digitalisation, synergy with global SDGs (SDGs 1 and 8), and the integration of technical assistance. This research provides an evidence-based framework for regulators and zakat institutions to integrate financial distribution with a non-financial supporting ecosystem